A diagnostic framework to assess the governance of the São Francisco River Basin Committee, Brazil. Issue 1 (31st May 2020) - Bouckaert, Frederick Willem; Vasconcelos, Vitor Vieira; Wei, Yongping; Empinotti, Vanessa Lucena; Daniell, Katherine Anne; Pittock, Jamie
Abstract: Environmental governance requires integrating social‐institutional governance and river basin management as part of the sustainable river basin development. This remains challenging and few tools exist to facilitate this objective. As part of a diagnostic governance framework on basin management in the São Francisco River Basin in Brazil, this paper investigates the influence of four governance indicators of institutions, leadership, collaboration, and learning . Data on governance and biophysical condition were collected through semi‐structured stakeholder interviews and indicator scoring. Institutions were found to be robust and based on shared values, despite adherence to different paradigms (top‐down vs. bottom‐up) and lack of transparency and clarity of roles. It was found that leadership, and its function of decision making, required enhanced subsidiarity and autonomy for the river basin committee. Collaboration was based on mutual respect, but needed to be improved to achieve fairer water allocation and payments, social justice, and ecological sustainability. It was found that learning requires better knowledge transfer and capacity building at municipal level. The current São Francisco Basin Plan (2016–2025) will build on a robust history of capacity building, but should include governance indicators for performance evaluation of environmental governance. 摘要: 环境治理要求将社会‐机构治理和流域管理融入可持续流域发展。这一任务依然具有挑战性，并且能够促成这一目标的现有工具很少。作为巴西圣弗朗西斯科河流域管理诊断框架的一部分，本文研究了四个治理指标的影响，这四个指标分别是机构、领导力、协作和学习。通过对利益攸关方进行半结构化面谈和指标评分，收集了有关治理和生物物理情况的数据。发现机构指标尽管遵循不同范式（自上而下式和自下而上式）、缺少透明度、缺少角色阐述，但却是稳健的且基于共享价值观。发现领导力指标及其决策功能要求为流域委员会提升辅助性原则和自治权。协作指标是在相互尊重的基础上进行的，但需要提升指标以实现更公平的水资源分配和水费、社会正义以及生态可持续性。发现学习指标要求自治区进行更佳的知识转移和能力建设。现行的圣弗朗西斯科河流域计划（São Francisco Basin Plan）（2016‐2025）将以一个稳健的能力建设历史为基础，但应将治理指标考虑在内，以进行环境治理表现评价。 Resumo: A governança ambiental requer a integração da governança socioinstitucional e a gestão de bacias hidrográficas como caminho para o seu desenvolvimento sustentável. Isso continua sendo um desafio e existem poucos instrumentos para auxiliar a alcançar esse objetivo. Como parte de um esquema diagnóstico de governança para a Bacia do Rio São Francisco, no Brasil, este artigo investiga a influência de quatro indicadores de governança: instituições, liderança, colaboração e aprendizado . Dados sobre governança e condições biofísicas foram coletados por meio de entrevistas semiestruturadas e valoração de indicadores com atores interessados. O indicador relativo a Instituições foi considerado o mais robusto e baseado em valores compartilhados, apesar da aderência a distintos paradigmas ("de cima para baixo", versus "de baixo para cima") e uma falta de transparência e clareza dos papéis. Observou‐se que a Liderança, bem como sua função para tomada de decisões, requer aperfeiçoamento da subsidiariedade e autonomia para o comitê de bacia. A Colaboração baseou‐se no respeito mútuo, mas necessita ser aprimorada para atingir alocação e pagamento pela água mais justos, assim como justiça social e sustentabilidade ecológica. O Aprendizado requer melhor transferência de conhecimento e capacitação em nível municipal. Palavras‐chave: comitê de bacia, indicadores diagnósticos, Bacia do Rio São Francisco, Governança Hídrica, Restauração dos rios. Resumen: La gobernanza ambiental requiere la integración de la gobernanza social‐institucional y la gestión de las cuencas hidrográficas como parte del desarrollo sostenible de las cuencas hidrográficas. Esto sigue siendo desafiante y existen pocas herramientas para facilitar este objetivo. Como parte de un marco de diagnóstico de gobernanza sobre la gestión de cuencas en la cuenca del río São Francisco en Brasil, este documento investiga la influencia de cuatro indicadores de gobernanza de instituciones, liderazgo, colaboración y aprendizaje. Los datos sobre la gobernanza y la condición biofísica se recopilaron a través de entrevistas semiestructuradas con las partes interesadas y la calificación de los indicadores. Se encontró que las instituciones eran robustas y se basaban en valores compartidos, a pesar de la adhesión a diferentes paradigmas (de arriba abajo versus de abajo hacia arriba) y la falta de transparencia y claridad de roles. Se descubrió que el liderazgo, y su función de toma de decisiones, requería una mayor subsidiariedad y autonomía para el comité de cuenca. La colaboración se basaba en el respeto mutuo, pero era necesario mejorarla para lograr una asignación y pagos de agua más justos, justicia social y sostenibilidad ecológica. Se descubrió que el aprendizaje requiere una mejor transferencia de conocimiento y desarrollo de capacidades a nivel municipal. El actual Plan de la Cuenca de São Francisco (2016–2025) se basará en una sólida historia de desarrollo de capacidades, pero debe incluir indicadores de gobernanza para la evaluación del desempeño de la gobernanza ambiental.